PENGARUH PEMROSESAN INFORMASI SECARA SENTRAL DAN PERIFERAL “PESAN SOCIAL MEDIA” TERHADAP KEPUTUSAN MEMILIH JASA JNE DI JAKARTA BARAT - Ramadhani, Nadhilah; Tri Atmodjo, Juwono (Universitas Mercu Buana, 2020)
The development of technology today, Social Media has become a tool used by companies to help prospective customers process information that suits their needs. Companies that utilize social media as marketing tools are PT. Tiki Line Nugraha Ekakurir, better known as JNE. JNE uses Instagram to provide information. This study is to determine the extent of the influence of Central Information Processing